2001
DOI: 10.1007/s00335-001-2076-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of members of the Wnt signaling pathway in the embryonic pituitary gland

Abstract: Prop1 is one of several transcription factors important for the development of the pituitary gland. Downstream targets of PROP1 and other critical pituitary transcription factors remain largely unknown. We have generated a partial expression profile of the developing pituitary gland containing over 350 transcripts, using cDNA subtractive hybridization between Prop1(df/df) and wild-type embryonic pituitary gland primordia. Numerous classes of genes including transcription factors, membrane associated molecules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 29 publications
3
56
0
Order By: Relevance
“…A recent report demonstrated that TCF7L2 is expressed in pancreatic beta cells [13]. Thus, by affecting the WNT signalling, the variant could influence the beta cell proliferation (and hence insulin secretion) that normally takes place during pregnancy [33,35]. The effect size for gestational diabetes mellitus conferred by this variant is similar to that reported in patients with type 2 diabetes [12].…”
Section: Tcf7l2 Rs7903146mentioning
confidence: 59%
See 1 more Smart Citation
“…A recent report demonstrated that TCF7L2 is expressed in pancreatic beta cells [13]. Thus, by affecting the WNT signalling, the variant could influence the beta cell proliferation (and hence insulin secretion) that normally takes place during pregnancy [33,35]. The effect size for gestational diabetes mellitus conferred by this variant is similar to that reported in patients with type 2 diabetes [12].…”
Section: Tcf7l2 Rs7903146mentioning
confidence: 59%
“…TCF7L2, which maps to chromosome 10q25.3, is a transcription factor belonging to the high mobility group-box transcription factors family [34]. It is involved in the wingless-type MMTV integration site family (WNT) signalling pathway, which is important for the development and growth regulatory mechanisms of the cell [35]. The TCF7L2 rs7903146 variant was originally associated with type 2 diabetes in individuals from Iceland, Denmark and the USA [12].…”
Section: Tcf7l2 Rs7903146mentioning
confidence: 99%
“…Knockout of Wnt5a leads to a dysmorphic gland, but endocrine cell specification is almost not affected (Cha et al 2004, Potok et al 2008. FZD2 is also expressed in the RP progenitor cells (E12.5), which renders these cells sensitive to the prevailing WNT ligands (Douglas et al 2001, Potok et al 2008. Wnt4 and Fzd2 continue to be upregulated in the neonatal stem cell compartment as compared to the adult SC-SP, which may be associated with the activated status of these cells during neonatal maturation (Table 1).…”
Section: :3mentioning
confidence: 99%
“…In the developing HP axis, this pathway coordinates proliferation of RP progenitors and differentiation of hormone-producing cells (34)(35)(36)(37)(38)(39)(40)(41). TCF7L1 has been shown to play critical roles in maintenance of stem cell pluripotency (42,43), tissue homeostasis of the skin epithelia (44), cell lineage determination during gastrulation (45,46), and brain development in vertebrates (47,48).…”
Section: Significancementioning
confidence: 99%